2023
DOI: 10.1007/s10681-022-03147-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in early maturity Chinese and European elite soybeans: A comparative analysis

Abstract: Soybean (Glycine max [L.] Merr.) is a legume crop important for global food security due to supplying high-quality vegetable protein and oil. China is the origin and rich center of soybean genetic diversity represented by numerous landraces and other genetic resources. During the nineteenth and twentieth centuries, world-wide dissemination of plant introductions laid the foundation of modern soybean production. Due to selection for regional adaptation, present-day elite soybean cultivars do have a comparativel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Our study employed 140 elite Chinese and European early-maturity soybeans to mine the key gene related to the active accumulated temperature. The genotype panel was well structured and the diversity of the collection ranged widely [13]. An area was identified upstream of the E1 locus at chromosome 6, which contained 16 genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study employed 140 elite Chinese and European early-maturity soybeans to mine the key gene related to the active accumulated temperature. The genotype panel was well structured and the diversity of the collection ranged widely [13]. An area was identified upstream of the E1 locus at chromosome 6, which contained 16 genes.…”
Section: Discussionmentioning
confidence: 99%
“…A set of 140 early-maturity soybean varieties was collected for the present study (see descriptive information in Supplementary Table S1, and Yao et al 2023) [13]. The total set consisted of 63 Chinese (CN) and 77 European (EU) elite cultivars.…”
Section: Elite Soybean Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The white flower Karawang local variety is planted in paddy fields in Tamanmekar Village, Pangkalan District, Karawang Regency, West Java Province According which is located at an altitude of 85 meters above sea level and the soil type is Grumosol (BP3K Pangkalan District, 2010). The climate type for Tamanmekar Village, Pangkalan District, Karawang Regency is type C (Slightly Wet) (Yao et al, 2023;Gholivand et al, 2021a). The plant materials of this research were 144 soybean genotypes from different ripening groups (early, medium and late) which were obtained from the Biogen Research Institute gene bank.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have confirmed that SSR markers are a convenient tool to identify genetically diverse soybean breeding materials and broaden the genetic background of available germplasm [25]. The genetic diversity associated with PH is particularly interesting because it influences various agronomic traits, including lodging resistance, light interception, and nutrient utilization [12,25,26]. Additionally, identifying SSR markers associated with PH and yield can contribute to the development of high-yielding soybean cultivars by facilitating a marker-assisted selection (MAS) approach [12].…”
Section: Introductionmentioning
confidence: 99%